Evaluation of Frenchbean germplasm against angular leaf spot - and ASHOK K. SHARMA, S.K. GUPTA, K.A MATHEW, K.R. SHYAM (Indian Phytopathology, 2002)
Crosses were made between 2 spot blotch resistant and 3 susceptible varieties of spring wheat. Analysis of the F1 and F2 generations showed that inheritance of spot blotch resistance is controlled by two pairs of complementary recessive genes.